DIFFERENTIAL DIAGNOSIS BETWEEN RADICULAR CYST AND GRANULOMA USING CONE-BEAM COMPUTED TOMOGRAPHY AND ULTRASONOGRAPHY: A SYSTEMATIC REVIEW - Carvalho, Ana Victória Moreira de; Muniz, Iasmin Miguel; Santo, Isabella Lopes do Espírito; Lima, Karen Jhulya de Morais Luciano; Silva, Raphael da; Guedes, Orlando Aguirre (CIPEEX, 2024)
Pulp tissue necrosis followed by colonization and infection of the root canal are determining events in the development of apical periodontitis. Radicular cysts and granulomas represent the most prevalent inflammatory periapical pathologies. This systematic review was conducted to analyze the possibility of performing a differential diagnosis between radicular cysts and granulomas using cone-beam computed tomography (CBCT) and ultrasonography (US). Searches were conducted in six electronic databases and three additional platforms for gray literature. All searches were performed up to May 15, 2021. A total of 1,111 studies were identified after duplicate removal. In phase 1, 35 studies were selected for full-text reading. In phase 2, 30 articles met the eligibility criteria and were included in this review, comprising 23 observational clinical studies and 7 case reports. There was significant variability in the methodological designs of the studies: various devices, protocols, and studied variables. The CBCT’s ability to establish a differential diagnosis for radicular cysts ranged from 60% to 80%, and for granulomas from 44% to 63%, while ultrasonography demonstrated 77% to 100% concordance for cyst diagnosis and 50% to 77% for granuloma diagnosis. The risk of bias in the studies was classified as low to moderate. CBCT and ultrasonography examinations enable the differential diagnosis between inflammatory periapical pathologies.